Phenotypes optimized for early‐life reproduction exhibit faster somatic deterioration with age, revealing a latent cost of high condition. (7th September 2016) - Adler, M. I.; Telford, M.; Bonduriansky, R.
Abstract: High condition enables individuals to express a phenotype with greater reproductive potential. However, life‐history theory predicts that reproduction will trade off with somatic maintenance and viability, and several studies have reported faster age‐related decline in performance in high‐condition individuals, suggesting that high condition in early life is associated with accelerated somatic deterioration. This trade‐off may be especially pronounced in males, which often express condition‐dependent secondary sexual traits that can impose viability costs during development and through damage‐inflicting adult sexual behaviours. To test this prediction, we reared larvae of the neriid fly Telostylinus angusticollis on diets of varying nutrient content and quantified somatic deterioration in solitary males, males housed in all‐male or mixed‐sex groups and immobilized males subjected to mechanical stress. We found that males reared on a nutrient‐rich larval diet (high‐condition males) suffered a higher rate of somatic deterioration with age, particularly when housed in groups. Perhaps as a result of accelerated somatic deterioration, high‐condition males did not outlive low‐condition males. In addition, high‐condition males housed in all‐male groups experienced a greater reduction in escape response with age than males housed in mixed‐sex groups, suggesting that male–male combat promotes somatic deterioration. However, even when immobilized, high‐condition males were still found to be more susceptible to somatic damage than low‐condition males. Our findings suggest that a high‐condition male phenotype is more prone to somatic damage, both as a result of associated behaviours such as combat, and because of the inherent fragility of the high‐condition body.